Numerical modelling of intra-wave sediment transport on sandy beaches using a wave-resolving, non-hydrostatic model - Mancini, Giulia (2021)
The mutual feedback between the swash zone and the surf zone is known to affect morphodynamic processes, such as breaker bars formation and migration on sandy beaches. To resolve this feedback in a process-based manner, the morphodynamics in the swash zone and due to swash-swash interactions must be explicitly solved, e.g., by using wave-resolving numerical models. Currently, few existing models are able to resolve the complex morphodynamics in the swash zone of sandy beaches, and none is practically applicable for engineering practice. Wave-resolving models can be depth-averaged or depth-resolving. The former type requires lower computational cost compared to the latter one, therefore, it is preferred for engineering purposes. This research work aims at improving the numerical modelling of the intra-wave sediment transport on sandy beaches, and in turn, of the exchange of sediments between the swash and surf zones under extreme events (e.g., storms, clusters of storms and tsunamis). A non-hydrostatic, wave-resolving model based on the open-source depth-averaged Non-hydrostatic XBeach framework is developed. An intra-wave advection-diffusion equation for the suspended sediment concentration, including erosion and deposition rates, is newly implemented in the model. A wave breaking-generated turbulence model together with a near-bed turbulence model are also developed. The effects of turbulence are included in both the hydrodynamics and sediment transport governing equations by means of the bed shear stress modelling. The newly implemented sediment transport and wave breaking-induced turbulence models are verified with a semi-analytical solution and existing laboratory experiments, respectively. The hydro-morphodynamics model herein proposed is then validated with data of laboratory experiments for three test cases. The first two case studies consist of simulating i) bichromatic waves groups and ii) consecutive, isolated solitary waves over sloped sandy beaches. In the former swash-swash interactions are clearly present. The third test case involves plunging breaking waves over a barred sandy beach. Numerical results show an improvement in the prediction of the intra-wave sediment transport, and in turn, of bed changes, especially in the swash zone with respect to the available sediment transport formulations in Non-hydrostatic XBeach. However, the process of the breaker bar development is not accurately predicted yet by the model herein developed. In particular, results indicate that for monotonic sloping beaches the model performs better when the initial bed profile is closer to the equilibrium compared to an initial uniform sloped bed. Instead, for different bed configurations, e.g., where a long bore-like propagation is allowed to develop, the proposed model shows a poor response in terms of velocity and morphodynamics modelling. The need of including additional physical processes to better capture the sediment transport in addition to the lack of modelling processes that have a vertical structure (i.e., vertical structure of the flow and sediment concentration) are highlighted in this thesis.